2002
DOI: 10.1021/jp013431s
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Mechanism for Primary Charge Separation in the Reaction Center of Rhodobacter Sphaeroides

Abstract: Geometry, reorganization energy, and vibrational and electronic spectra of pigment molecules in bacterial photosynthetic reaction centers (Rhodobacter sphaeroides) are determined using quantum chemical methods. B3LYP calculations on a slightly truncated form of bacteriochlorophyll a give vibrational modes at 23, 40, 64, and 128 cm -1 , which we conclude correspond to those seen in resonance Raman (RR) spectra of reaction centers with labeled cofactor atoms, and, as oscillations, in optical transient spectra. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 70 publications
2
20
0
Order By: Relevance
“…The nature of the oscillations is uncertain. Motions in the protein, 21,22 in the cofactors and their side groups 10 have been suggested. [23][24][25][26] Coupled motion between the two monomers in the special pair (SP), producing a rich dimer resonance Raman spectrum 27,28 and introducing oscillations in the energy of the P* state relative to the charge separated P + B A -state, is another very likely source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the oscillations is uncertain. Motions in the protein, 21,22 in the cofactors and their side groups 10 have been suggested. [23][24][25][26] Coupled motion between the two monomers in the special pair (SP), producing a rich dimer resonance Raman spectrum 27,28 and introducing oscillations in the energy of the P* state relative to the charge separated P + B A -state, is another very likely source.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Coupled motion between the two monomers in the special pair (SP), producing a rich dimer resonance Raman spectrum 27,28 and introducing oscillations in the energy of the P* state relative to the charge separated P + B A -state, is another very likely source. 10,[22][23][24][25][26][27][28][29] Streltsov et al found a distinct oscillation at 12 ( 2 cm -1 and another at 30 ( 3 cm -1 . [16][17][18] More recently a 32 cm -1 oscillation was found in the work of Yakovlev et al and connected to ET.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that there is indeed an increase of electron density on B A during some time after excitation of P (see Refs. [20]). Recenty more accurate quantum chemical calculations (see Refs.…”
Section: Discussion Of Et In the Prc And Concluding Remarksmentioning
confidence: 99%
“…It was previously suggested [12] that modes with frequencies 80-150 cm -1 are due to vibrations of the protein environment. Now the prevailing opinion is that the corresponding vibration is localized on the P dimer (see, for example, [17,44,54,76,[78][79][80]). The authors of [80] believe that the initiator of electron transfer is out-of-plane vibration of the acetyl side group of ring I.…”
mentioning
confidence: 99%
“…The temperature dependence of the halfwidth of the P870 and P960 bands are not described by the relation Γ(T) = Γ 0 + γ 0 coth 2 (θ/T) characteristic for h µ modes (see the examples of their appearance in [17]). Therefore the explanation in [80] seems quite dubious.…”
mentioning
confidence: 99%